The Earth and its electric field - Yakymchuk, M.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
The information about the main results of scientific researches, obtained by the author recently, is presented. A model of the structure of Earth's and atmosphere's electric field is analyzed. Many natural phenomena cannot be explained with the division of the actions of mechanics, fluid dynamics, and electrodynamics. This requires a model of the full interaction of all the fields. The interdependence between electrical charge, temperature and pressure, which makes it possible to explain many phenomena observed in the nature, is established.